Giving dates to young women for the prevention of anemia - Indryani, Indryani; Mustar, Mustar; Hasnidar, Hasnidar; Pattola, Pattola; Sulfianti, Sulfianti (Lembaga Penelitian dan Pengabdian Masyarakat,Politeknik Sandi Karsa, 2025)
Anemia prevalence among adolescent girls is significantly higher compared to boys, primarily due to menstruation and increased iron requirements during growth. This condition negatively affects immunity, concentration, academic performance, physical fitness, and productivity, and poses long-term health risks, particularly during future pregnancies. In Bone Regency, adolescent anemia rates remain high despite the government’s iron supplementation program. This community service program aimed to implement research findings on using dates (Phoenix dactylifera) to increase hemoglobin levels and address anemia among adolescent girls. The activity involved health education on anemia prevention and the daily provision of 100 grams of dates (7–8 pieces) for seven consecutive days during menstruation. The program was conducted through observation, counseling sessions, and hemoglobin monitoring before and after the intervention. The rationale for using dates is based on their high iron and nutrient content, which supports hemoglobin synthesis naturally. The targeted participants were adolescent girls from the community surrounding Lapatau Stadium, Bone Regency. Expected outcomes included increased knowledge regarding anemia prevention, improvement in hemoglobin levels, and the promotion of alternative nutritional interventions for anemia management. Monitoring and evaluation were conducted by measuring hemoglobin levels post-intervention to assess effectiveness. The program also aims to disseminate results through a SINTA 5-indexed journal publication, providing evidence-based recommendations for integrating date consumption into adolescent nutrition programs. This initiative highlights the potential of locally acceptable, culturally relevant food-based strategies to complement existing public health interventions in reducing anemia prevalence among teenage girls.